(untitled) (Theatrum historiae, 2008)
Hermengild Shkorpil is the sixth of the 13 children of Vaclav Shkorpil Sr. and Anna born Irechekova. Hailing from High Duty, he studied natural sciences in Prague and Leipzig. He specialized in mineralogy and ethnology, but his research interests are or much wider. In 1880 he went to Eastern Rumelia to create, together with other Czech pedagogues, the basis of secondary education in the young Bulgarian state, which in 1878 was liberated from Turkish rule. Shkorpil worked in the men’s and girl’s high schools in Plovdiv (1880-1881), Sliven (1881-1886), Sofia (1886-1894), Ovdiv (1894-1900), Ruse (1900-1904) and Varna (1904-1906) where he retired at his own request. In high schools he taught various natural sciences, he created natural science and archeological collections for them. He is also the founder of several natural science, archeological and museum associations. Since his arrival in Bulgaria he has been working on a textbook on the geography of Bulgaria, researching Plovdiv waters, working on the geological map of southern Bulgaria, paying attention to speleology, natural mysteries (petrified forest near Varna, moving sands called Golden Sands) and others. He published the results of his research and observations alone or with his brother Karel. During his stay in Varna he was the first chairman of the Varna Archaeological Club (1905-1923), managed the publishing activities of the club and the Varna Museum, where he was museum manager, and lectured on the results of his archaeological and historical research. He was buried next to the early Christian basilica on Zmiyski Vrah (Ilan Tepe and Janavara Tepe) near the village of Janava (now part of Varna).